PENYELESAIAN PERKARA SENGKETA TANAH PADA BADAN PERTANAHAN NASIONAL KOTA JAMBI - Abdul Hariss (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Because of the soil is very important for the implementation of the business or to establish a residence and / or place of business sometimes citizens who have a desire to land the highly bazaar forget to acreage or deliberately exaggerate the land boundary to other people's land area. On the other hand sometimes citizens who have a very extensive land boundary lies the forgotten land and not care about it or do not manage the land in full. At some point after the interest on a land boundary issues arise where landowners feel aggrieved that some land has been managed and owned by others with evidence terpancangnya new land boundary markers that previously did not exist or did not know or people who have marked out a new one considers pebuatannya is true with documentary evidence of legal land ownership available to it.In because of land certificates issued by the National Land Agency of Jambi to the case of a dispute shall be held responsible in the early stages of dispute resolution is the National Land Agency of the city of Jambi.In the settlement of the land boundary by the National Land Agency Jambi is not easy because many constraints faced.Keyword :  cases, land disputes